If a+b+c=1, a b+b c+c a=2 and a b c=3,


If $a+b+c=1, a b+b c+c a=2$ and $a b c=3$, then the value of $a^{4}+b^{4}+c^{4}$ is equal to


$a^{2}+b^{2}+c^{2}=(a+b+c)^{2}-2 \Sigma a b=-3$

$(a b+b c+c a)^{2}=\Sigma(a b)^{2}+2 a b c \Sigma a$

$\Rightarrow \Sigma(a b)^{2}=-2$

$a^{4}+b^{4}+c^{4}=\left(a^{2}+b^{2}+c^{2}\right)^{2}-2 \Sigma(a b)^{2}$


Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now